Facilitating the whole teaching-learning process in physical education throught the use of cues - Javier Fernández-Rio; Antonio Méndez-Giménez (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2013)
Teachers search for instructional strategies that would allow them to optimize the existing time to maximize students’ learning. They are capable of perceive and retain only a limited amount of information. Therefore, the selection and transmission of critical information is one of the most important teacher roles to make students receive accurate data on the skill to learn. A learning cue could be defined as a short, precise sentence (even words) that portrays effectively the important elements of a task/ability. Students can remember them effectively in and out of the class. Learning cues can be introduced in different formats (verbal, non-verbal, motor, visual...) and they can be developed by the teacher or the student. Its use in peer-teaching and peer-assessment procedures allow students to verbal, motor and mentally rehearse all the critical information provided by the cues, while they practice or give feedback to their classmates